Hybridization Technique in Tartary Buckwheat (Fagopyrum tataricum Gaertn) - Joshi, Bal K.; Bimb, Hari P.; Okuno, Kazutoshi (Nepal Agriculture Research Journal, 2014)
N/A Nepal Agric. Res. J. Vol. 9, 2009, pp. 118-128 DOI: http://dx.doi.org/10.3126/narj.v9i0.11650